CONTEMPORARY THEORETICAL CONCEPTS OF STRESS (Annual of the Faculty of Philosophy in Skopje, 2007)
The complex nature of stress and different reaction caused by stress, are the basic reason for emerging of great number of theories attempting to define stress. In the analysis of the current theoretical concepts we have concluded that more of them in the defining of the term consider one of its components: biological, physiological or psychological Aware that non of the conceptions, regardless of how complete they are in its definition, cannot encompass all of the components of this complex phenomenon, the goal of this abstract is, through comprehensive analysis, to give a review of contributions and shortfalls of most important theories.Several most important physiological theories and cognitive- behavioral concepts were analyzed. Special accent was given to the psychological model of stress as most comprehensive conception that incorporates most of the components of stress. Finally, we have concluded that the phenomenon of stress is hard to define, therefore non of the definitions is final or satisfying.
Keywords: STRESS; STRESSFUL